Awareness and endorsement of vietnamese character stereotypes among filipino and japanese students = Nhận thức và quan điểm đối với các định kiến về tính cách người việt nam của sinh viên phi-líp-pin và nhật bản - Châu, Hồng Quang (ĐHQGHN - Trường Đại học Ngoại Ngữ, 2021)
Very little research has examined stereotypes of Vietnamese people. This study attempts to fill this gap by exploring the awareness, or the lack thereof, of Vietnamese stereotypes and the endorsement or rejection of such stereotypes by Filipino and Japanese students in University of the Philippines, Diliman. Questionnaires and interviews were conducted among 15 Filipino and 15 Japanese students, and in the questionnaire, the checklist method in the classic study by Katz and Braly (1933) was employed. Responses showed that the Vietnamese stereotypes known by the two groups were very similar, largely based on circulating Asian and Chinese stereotypes revealed by previous studies. However, the participants claimed to possess very limited knowledge of Vietnamese character. Stereotype transmission was considered to have been facilitated by education, history, media and hearsay, which triggered vastly different images of Vietnamese people. On the other hand, their personal beliefs about the Vietnamese revealed some characteristics that deviates from common Asian stereotypes revealed by the literature. Personal contact with Vietnamese people tended to confirm and create positive beliefs among the Japanese students, while the Filipino participants, who generally had very limited contact with the Vietnamese, were strongly influenced by the media. Implications are also recommended for international communication between Vietnamese people and other groups.